Retrospective Analysis on Intraoperative Neuromonitoring (IOM) of Potential Nerve Injury in Scoliosis Correction Surgery - Omat Rachmat; Dohar AL Tobing; Ilma Fiddiyanti; Rr. Nur Fauziyah; Jenifer Kiem Aviani; Rr. Anisa Siwianti Handayani (Faculty of Medicine, Universitas Padjadjaran, 2021)
Iatrogenic spinal injury resulting in paraplegia or paraparesis after surgical correction of scoliosis deformity is a rare complication but is very detrimental to the patient. Intraoperative Neuromonitoring (IOM) has become the gold standard to monitor surgical procedures which has potential risks to damage the spinal cord. This study aimed to retrospectively analyze the role of IOM in predicting the severity and extent of neurological injury during and after spinal correction surgery in adult idiopathic scoliosis cases related to surgical variables. This was a retrospective cohort study conducted at Dr. Cipto Mangunkusumo National Central Hospital, Fatmawati Central Hospital, and dr. Drajat Prawiranegara General Hospital during the period of 20 March 2018 to 20 August 2019. The primary outcomes were intraoperative monitoring status and post-operative neurological deficits status. Confounder data on scoliosis correction degree, intraoperative hemorrhage, and type of anesthesia used during surgery were retrieved. Chi-Square statistic was used in the analysis. Out of the ninety three patients eligible for this study, twenty two patients was detected as positive in IOM assessment. Four of the patients were found to be positive for post-operative neuromuscular defect. Thereby it can be concluded that IOM procedure can effectively prevent neurological deficits post-surgery with 81.8% specificity and 95.7% sensitivity among thosepositively detected by IOM. Some of the factors that could potentially influence false positive IOM results such as anesthetic used; dosage and administration procedures; magnitude of the scoliosis correction angle; and amount of bleeding during surgery have to be carefully analyzed.